Greening work: labor market policies for the environment - Katharina Bohnenberger (Empirica, 2022)
Jobs are essential for social inclusion, raising taxes, and guaranteeing the financial resilience of (welfare) states. At the same time, the Sustainable Development Goals, the Paris Agreement, and the European Green Deal require the greening of our economies and labor markets. This paper assesses how labor market policies can green employment. The paper analyses the potential effects of eight different policy strategies on four dimensions of the Taxonomy of Sustainable Employment: conversion of plants and businesses, environmental labor law, climate decommodification, socio-ecological job guarantee, vocational guidance and retraining, distribution of employment time, alternative income sources, and equalization of income. All eight strategies have the potential of greening employment but feature different intensities in the four dimensions. In the light of environmental crises, the results suggest widening the toolbox of labor market policies for a green and just transition.
Keywords: 330; Employment; Work; Sustainability; Climate policy; Just transition; Socio-ecological transformation; SDGs